Engineering students as perspective human resources of small industrial entrepreneurship - Andras, Iryna A. (Journal of the Belarusian State University. Sociology, 2019)
The article is focused on the development of small industrial entrepreneurship in Belarus. Analysis of statistical data shows that in the context of domination of large industrial enterprises, the share of small industrial enterprises is 90 % with revenue of no more than 10 % of volume of industrial production in the republic. This fact indicates the need to increase the efficiency of their activities. We studied the potential of engineering students in development of entrepreneurship in industry by sociological methods. The survey of engineering students shows that practice-oriented training is one of the main factors that would help them to open their business in the production sphere. At the same time, students consider getting business knowledge rather as an extension of their worldview and adaptation to the market conditions of work than for the organization of industrial entrepreneurship. We proposed measures to activate the involvement of engineering students in industrial business.
Keywords: industrial entrepreneurship; business education; engineering students; small industrial enterprises